Social Inequalities and Depressive Symptoms in Adults: The Role of Objective and Subjective Socioeconomic Status - Hoebel, Jens; Maske, Ulrike E.; Zeeb, Hajo; Lampert, Thomas (PloS one, 2017)
There is substantial evidence that lower objective socioeconomic status (SES)-as measured by education, occupation, and income-is associated with a higher risk of depression. Less is known, however, about associations between perceptions of social status and the prevalence of depression. This study investigated associations of both objective SES and subjective social status (SSS) with depressive symptoms among adults in Germany. Data were obtained from the 2013 special wave of the German Health Update study, a national health survey of the adult population in Germany. Objective SES was determined using a composite index based on education, occupation, and income. The three single dimensions of the index were also used individually. SSS was measured using the MacArthur Scale, which asks respondents to place themselves on a 10-rung 'social ladder'. Regression models were employed to examine associations of objective SES and SSS with current depressive symptoms, as assessed with the eight-item Patient Health Questionnaire depression scale (PHQ-8 sum score ≥10). After mutual adjustment, lower objective SES and lower SSS were independently associated with current depressive symptoms. The associations were found in both sexes and persisted after further adjustment for sociodemographic factors, long-term chronic conditions, and functional limitations. Mediation analyses revealed a significant indirect relationship between objective SES and depressive symptoms through SSS. When the three individual dimensions of objective SES were mutually adjusted, occupation and income were independently associated with depressive symptoms. After additional adjustment for SSS, these associations attenuated but remained significant. The findings suggest that perceptions of low social status in adults may be involved in the pathogenesis of depression and play a mediating role in the relationship between objective SES and depressive symptoms. Prospective studies are needed to establish the direction of effects and to address questions of causality.